Reducing brown rot and maintaining plum quality during cold storage with composite edible coatings containing avocado seed extract - Souza, Ricardo-Lima-de; Asgarian, Zahra Sadat; Pérez-Gago, María B.; Palou, Lluís (2023)
Reduction of brown rot, caused by Monilinia fructicola, is a major challenge in the postharvest storage of fresh Japanese plums (Prunus salicina Lindl.), which are highly perishable. The use of plant extracts with antifungal properties could be a sustainable natural alternative to polluting chemical fungicides for brown rot control. An extract obtained from avocado seeds (AVS) was found to completely inhibit the in vitro fungal growth of M. fructicola. This extract was then incorporated into composite edible coating matrixes based on hydroxypropyl methylcellulose (HPMC) or Arabic gum (AG) as hydrocolloids and beeswax as lipid. Coated fruits were stored for 5 weeks at 1 °C, followed by 3 days at 7 °C and 5 days of shelf life at 20 °C, simulating cold storage, transportation, and shelf life, respectively. After cold storage, the HPMC-AVS and AG-AVS coatings reduced disease incidence by 30% with respect to uncoated control fruit and disease severity by 50 and 62%, respectively. After shelf life, AG-AVS significantly reduced disease incidence and severity by 13 and 42%, respectively. The coatings also reduced the fruit respiration rate, preserved fruit firmness and alleviated chilling injury symptoms. Additionally, the coatings had no impact on the fruit physicochemical and sensory quality, and AG-AVS improved fruit gloss. These findings show the potential of composite edible coatings incorporating AVS extract to reduce brown rot and preserve plum postharvest quality.